After the reformsaan analysis of the factors associated with the use of legal services in child welfare proceedings in Ireland - Edel Walsh; Aileen Murphy; Carmel Halton; Gill Harold (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
Against the backdrop of austerity measures and public sector reforms in Ireland, this paper examined legal costs incurred in child welfare proceedings by the State Child and Family Agency - Tusla, using a need-based allocation model. The direct financial costs of engaging with legal services, necessitated by the adversarial nature of child welfare proceedings, were scrutinized to determine if resources were allocated based on need. Adopting a cross-sectional research design, secondary data (obtained from the organization's financial billing system. n =1032) were employed in an econometric analysis examining the factors influencing variations in Tusla's legal expenditure. The dependent variable was total amount billed by legal firm per observation and the independent variables included type of legal activity involved (a proxy for need), geographical location and type of legal personnel (supply factor). Type of legal personnel, volume and type of legal activity have significant positive effects on legal spend. Administrative area does not significantly affect spending on legal services. We found that engagement with legal services, demanded by the adversarial nature of child welfare proceedings, has considerable cost implications; however, does seem to be allocated on the basis of need. The findings can be employed to increase the organization's awareness of costs.
Keywords: H83; J13; P36; 330; Child protection; legal expenditure; public sector; Tusla; Ireland